Productive cycles and region in Peru: 1971-1981 - Iguiñiz Echevarría, Javier (1984)
The existence of regions in Peru is recognized from many different perspectives. The most basic of these divides territorial Peru into Coast, Sierra and Selva. There are still very powerful reasons to continue using this way of dividing the national territory. At a more theoretical level, we can resort to the regional classification proposed by Efraín Gonzales de Olarte from the point of view of the different degree of development of capitalism in the country.